AN INVESTIGATION OF APPROACHES TO TEACHING READING USED BY A TEACHER IN A JUNIOR HIGH SCHOOL IN BANDUNG - Rahmi, Gita (2014)
This study uses a qualitative descriptive design and adopts characteristics of a case study. The data are collected by using classroom observation for seven meetings where the researcher acts as non-participant observer, open-ended questionnaires which are delivered to the teacher and the students, interview with the teacher and the students as well and document analysis from students' progress test (also called ulangan harian). The teaching activities are analyzed and classified based on three teaching stages proposed by Wallace (1992). The findings reveal that the teacher uses an eclectic approach in teaching reading. The data can be discovered through reading activities conducted by the teacher which show that she teaches reading by applying review, brainstorming, preview and pre-reading questions in her pre-reading stage; silent reading, reading aloud, questioning, showing some texts and discussing the linguistic choices or features, vocabulary study and translating in her while-reading stages; and follow-up activity and retelling activity in her post-reading stages. Further, the teacher's problems in teaching reading are students' lack of participation, teacher's lack of theoretical knowledge of EFL teaching, vocabulary-oriented teaching and teacher-centered teaching. Moreover, the students have both positive and negative opinions on the activities. Some students find that the activities are interesting and challenging, while the other students think the activities are difficult and boring. Therefore, the activities affect the students' reading skills positively and negatively. The increase and decrease of students' scores for some skills presumably occur because texts, number of reading skills and number of questions tested in test 1 and test 2 are different. Based on the findings, it is suggested that the teacher considers the roles of curriculum, syllabus and lesson plan in teaching reading. Then, teacher should recognize the students' needs and conditions so she can apply the right activities in the appropriate context. Last, government should conduct training for the teacher about EFL teaching so the teacher's ability in teaching will be improved. Penelitian ini merupakan penelitian deskriptif dan kualitatif dan juga memiliki sifat-sifat seperti studi kasus. Data dikumpulkan melalui observasi sebanyak tujuh kali pertemuan yang mana peneliti hanya berperan sebagai pengamat, melalui kuesioner terbuka yang diberikan kepada guru dan para siswa, melalui wawancara yang dilakukan terhadap guru dan para siswa dan melalui dokumen yang diambil dari ulangan harian siswa. Aktivitas pengajaran dianalisis dan diklasifikasikan berdasarkan teori tiga tahapan pembelajaran reading yang dikemukakan oleh Wallace (1992). Hasil penelitian menunjukkan bahwa guru menggunakan pendekatan eklektik dalam pengajaran reading. Data bisa dilihat melalui kegiatan-kegiatan reading yang dilakukan guru yang menunjukkan bahwa dia mengajar reading dengan menerapkan review, brainstorming, preview dan pre-reading questions pada kegiatan pendahuluan; silent reading, reading aloud, questioning, showing some texts and discussing the linguistic choices or features, vocabulary study dan translating dalam kegiatan inti; dan follow-up activity dan retelling activity dalam kegiatan akhir. Selanjutnya, guru memiliki beberapa kendala dalam pengajaran reading seperti kurangnya pengetahuan guru mengenai pengajaran EFL, pengajaran yang berorientasi pada keutamaan penguasaan kosakata dan pengajaran yang terpusat pada guru. Kemudian, para siswa memiliki pendapat yang beragam, baik yang positif maupun negatif, terhadap kegiatan-kegiatan tersebut. Beberapa siswa menganggap kegiatan tersebut menarik dan menantang, namun siswa yang lainnya berpendapat bahwa kegiatan tersebut sulit dan membosankan. Lalu, kegiatan-kegiatan tersebut juga memberikan pengaruh positif dan negatif terhadap kemampuan siswa dalam membaca. Peningkatan dan penurunan nilai para siswa untuk beberapa skill dalam reading diyakini terjadi karena teks, jumlah skill dan jumlah pertanyaan yang diujikan pada tes 1 dan tes 2 berbeda. Berdasarkan hasil penelitian tersebut, guru disarankan untuk mengutamakan penggunaan kurikulum, silabus dan Rencana Pelaksanaan Pembelajaran (RPP) sebagai pedoman dalam pengajaran reading. Guru sebaiknya mengetahui keadaan dan kebutuhan para siswa sehinggga dia bisa menerapkan kegiatan yang sesuai